A progeroid syndrome caused by a deep intronic variant in TAPT1 is revealed by RNA/SI‐NET sequencing. Issue 2 (18th January 2023) - Nabavizadeh, Nasrinsadat; Bressin, Annkatrin; Shboul, Mohammad; Moreno Traspas, Ricardo; Chia, Poh Hui; Bonnard, Carine; Szenker‐Ravi, Emmanuelle; Sarıbaş, Burak; Beillard, Emmanuel; Altunoglu, Umut; Hojati, Zohreh; Drutman, Scott; et al.
Abstract: Exome sequencing has introduced a paradigm shift for the identification of germline variations responsible for Mendelian diseases. However, non‐coding regions, which make up 98% of the genome, cannot be captured. The lack of functional annotation for intronic and intergenic variants makes RNA‐seq a powerful companion diagnostic. Here, we illustrate this point by identifying six patients with a recessive Osteogenesis Imperfecta (OI) and neonatal progeria syndrome. By integrating homozygosity mapping and RNA‐seq, we delineated a deep intronic TAPT1 mutation (c.1237‐52 G>A) that segregated with the disease. Using SI‐NET‐seq, we document that TAPT1 's nascent transcription was not affected in patients' fibroblasts, indicating instead that this variant leads to an alteration of pre‐mRNA processing. Predicted to serve as an alternative splicing branchpoint, this mutation enhances TAPT1 exon 12 skipping, creating a protein‐null allele. Additionally, our study reveals dysregulation of pathways involved in collagen and extracellular matrix biology in disease‐relevant cells. Overall, our work highlights the power of transcriptomic approaches in deciphering the repercussions of non‐coding variants, as well as in illuminating the molecular mechanisms of human diseases. Synopsis: This study highlights the significance of non‐coding variants to uncover rare Mendelian human disorders and the power of combined transcriptomic analyses in identifying molecular pathological pathways. Patients presented with congenital, severe osteogenesis imperfecta and progeroid appearance. RNA‐seq and direct Sanger sequencing in patients' fibroblasts revealed a private TAPT1 deep intronic mutation leading to a protein‐null allele. TAPT1 deep intronic mutation triggers out of frame exon 12 skipped transcripts that are subject to nonsense‐mediated decay (NMD). Integrative RNA‐seq and SI‐NET‐seq analyses uncovered a dysregulation in collagen and extracellular matrix (ECM) pathways consistent with the patients' phenotypes. Abstract : This study highlights the significance of non‐coding variants to uncover rare Mendelian human disorders and the power of combined transcriptomic analyses in identifying molecular pathological pathways.